Company's innovativeness in transition economies: The case of Macedonia. - Bozhinovska, Tihona; Cvetanoska, Marijana; Denkovski, Dragan (Faculty of Economics, University of Banja Luka, 2015)
Innovation is the ultimate result of the organization activities related to learning and creating new knowledge. According to the economic literature, innovation is a primary source of growth and national progress. Innovativeness is also identified as crucial for organizational survival in today’s global economy. Innovation is the only option for companies that want to change, grow and sustain their competitive advantage. Although the importance of innovation for the organizational and economic growth is significantly emphasized and well-documented in the economic literature, only few studies have focused on company’s innovativeness in the transition economies from the south-east Europe. The aim of this study is to examine the level of innovativeness of Macedonian enterprises and to determine the connection between the enterprise’s innovation and organizational performance. The main hypothesis on which this paper is based is that there is a positive and significant association between organizational innovativeness and firm performance. The data were obtained from the Innovation Survey conducted by the State Statistical Office of the Republic of Macedonia. In the survey were included only enterprises that have ten (10) or more employees. This survey collected data on enterprise’s innovation activities for three-year period, 2010-2012. The analyses were based on the data provided by the 1,130 respondents. According to this survey results small number of Macedonian companies have managed to introduce innovation in the analyzed period. Most of the large companies are identified as innovative. Almost two thirds of the small companies are non-innovative. More than half of the medium sized enterprises are classified as innovative. The findings of our analysis have shown that there is a negative and statistically significant relation between goods innovations and revue growth rate. In addition, it was reported a positive and significant effect of the introduction of service innovations on revenue growth. Furthermore, we did not found a significant correlation between organization or marketing innovations and revenue. This study indicates that only product (goods or service) innovations have significant impact on revenue growth. Apart from the various limitations of the paper, we can conclude that some of the previous studies on the relation between organizational innovativeness and firm performance have similar findings
Keywords: organizational innovativeness, firm performance, types of innovations, Macedonian companies